KEWARGAAN DAN PARTISIPASI POLITIK PEMILIH DISABILITAS (Studi Kasus: Pemilihan Kepala Daerah Tahun 2020 di Tangerang Selatan) - Diah Rizka Larasati (2022)
This thesis aims to examine the factors causing the low political participation of persons with disabilities in the regional elections in South Tangerang City in 2020 using the concept of inclusive citizenship. The method used is a case study approach with data collection techniques in the form of in-depth interviews with six persons with disabilities, namely two visually impaired, two deaf and two physically handicapped. In addition, other informants were the Chairperson of the KPU and South Tangerang Bawaslu, the Chairperson of the Disability Organization in South Tangerang, and academics. The results of this thesis found that South Tangerang City was ranked first as the city with the highest Human Development Index (IPM) and was ranked second as the city with the best education in Banten Province. Unfortunately, this is not in line with the level of political participation of the voters. Several factors contributed to the low political participation of people with disabilities in the 2020 Tangsel Regional Head Elections, including: the data collection process, access to information and participation facilities that are not disability friendly and stigmatization/discrimination from the community.